Low-dimensional non-metal catalysts: principles for regulating p-orbital-dominated reactivity - Si Zhou (Nature Portfolio, 2021)
Abstract Activation of p-block elements to replace the rare and precious transition metals for renewable energy applications is highly desirable. In this review, we go over recent experimental and theoretical progress on the low-dimensional non-metal materials for clean energy production, including carbon, silicon, oxide, boron, and phosphorus-based nanostructures, with the p-block elements serving as active sites. We aim to elucidate the mechanism for triggering activity in different kinds of non-metal systems, and extract general principles for controlling the p-orbital-mediated reactivity from a theoretical point of view. The perspectives and challenges for developing high-efficiency non-metal catalysts are provided in the end.